Effectiveness of Varying Eggshell and Zeolite Thickness in Reducing Iron Content of Well Water in Jebugan, Klaten - Fitria Rizky Putri; Windi Wulandari (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Iron (Fe) levels in the human body can cause harm to both health and the environment which can cause public health problems. Fe levels based on the results of preliminary tests carried out in Jebugan Klaten Village were 2.58 mg/l, these results exceed the clean water quality standards for sanitation hygiene. One way that can be done is by a filtration process using egg shells and zeolite. The aim of this research is to determine the effect of variations in the thickness of egg shells and zeolite on reducing Fe levels in clean water in Jebugan Village, Klaten. This type of research is an experiment with a pre-posttest with control design. The research location was Jebugan Village, Klaten and filtration tests and measurements of iron levels were carried out at the Regional Health Laboratory of the Sukoharjo City Health Service. The research was carried out from September 2023 to February 2024. The number of samples required in this research is 28 liters. The processing uses filtration with varying thicknesses of egg shell and zeolite of 5 cm, 10 cm and 15 cm. Data analysis used the Shapiro-Wilk statistical test and One Way Anova. The results of the research showed that there was an influence of variations in the thickness of egg shell and zeolite on decreasing Fe levels (p-value of 0.001) with the average result of decreasing Fe levels for each thickness variation being 1.396 mg/l (3.45%); 0.887 mg/l (38.69%); 0.415 mg/l (71.34%); and 0.076 mg/l (94.76%). It is recommended that residents of Jebugan Village, Klaten use water treatment by filtration using zeolite and egg shells with a thickness of 15 cm so that the iron (Fe) content in the water meets health quality standards. Keywords: Eggshell, Zeolite, Iron Content